2016
DOI: 10.1111/pce.12830
|View full text |Cite
|
Sign up to set email alerts
|

Association between water and carbon dioxide transport in leaf plasma membranes: assessing the role of aquaporins

Abstract: The role of some aquaporins as CO permeable channels has been controversial. Low CO permeability of plant membranes has been criticized because of unstirred layers and other limitations. Here we measured both water and CO permeability (P , P ) using stopped flow on plasma membrane vesicles (pmv) isolated from Pisum sativum (pea) and Arabidopsis thaliana leaves. We excluded the chemical limitation of carbonic anhydrase (CA) in the vesicle acidification technique for P using different temperatures and CA concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 71 publications
2
22
0
Order By: Relevance
“…However, biological membranes appear to have a low CO 2 permeability [75] due to a high level of protein and sterol content [74,76]. Recently, using plasma membrane vesicles of pea leaves it has been demonstrated that plasma membrane aquaporins could facilitate CO 2 transport [77]. The same data were earlier presented for tobacco, Arabidopsis, fava bean, and others [78][79][80].…”
Section: Ca In the Plasma Membrane And Envelope Chloroplast Membrane mentioning
confidence: 60%
See 1 more Smart Citation
“…However, biological membranes appear to have a low CO 2 permeability [75] due to a high level of protein and sterol content [74,76]. Recently, using plasma membrane vesicles of pea leaves it has been demonstrated that plasma membrane aquaporins could facilitate CO 2 transport [77]. The same data were earlier presented for tobacco, Arabidopsis, fava bean, and others [78][79][80].…”
Section: Ca In the Plasma Membrane And Envelope Chloroplast Membrane mentioning
confidence: 60%
“…This connection allows CO 2 permeability across the plasma membrane to be facilitated. Further, the decrease in the CA concentration was shown to lead to a lower CO 2 permeability in plasma membrane vesicles [77]. Therefore, it can be proposed that the functioning of plasma membrane aquaporins depends on the CA activity under both normal and stress conditions.…”
Section: Ca In the Plasma Membrane And Envelope Chloroplast Membrane mentioning
confidence: 99%
“…The results are also difficult to reconcile with a publication from the same group suggesting that phosphorylation sites on both sides of the membrane are essential for the SLAC1 response to pCO 2 (Yamamoto et al, 2016). Thus, the relationships between aquaporins and carbonic anhydrases in water and CO 2 permeability are a matter of debate (Grondin et al, 2015;Zhao et al, 2016), as is their coupling to activation of the anion channel. For now, the guard cell CO 2 (HCO 3 2 ) sensors remain unknown, although it is clear that, downstream, the action overlaps with significant elements important also for ABA signaling (Chater et al, 2015;Tian et al, 2015).…”
Section: Table I Basic Biophysical Parameters Of Stomatal Guard Cellmentioning
confidence: 80%
“…Guard cells coordinate solute flux actively through a number of major transport pathways at the plasma membrane and the tonoplast during stomatal movements (Box 1;Allen et al, 1999;Chen et al, 2016;Desikan et al, 2002;Suhita et al, 2004;Yamauchi et al, 2016;Yin et al, 2009;Zhang et al, 2001;Zhao et al, 2016). Like all plant cells, guard cells use ATP to drive H + out of the cell via H + -ATPases, thereby generating a membrane voltage, negative inside, and an electrochemical potential difference (Dm H ) for the H + .…”
Section: Stomatal Openingmentioning
confidence: 99%
“…How plants release the root‐zone CO 2 to the atmosphere is an important question. To gain entry into plants, CO 2 could pass through aquaporins in the plasma membrane which have been shown to enhance membrane permeability to CO 2 (Hanba et al , Li et al , Zhao et al ) or directly through the lipid bilayer of the plasma membrane. After reaching the symplasm, CO 2 could diffuse through plants very quickly as evidenced by gas exchange measurements (Figs and ).…”
Section: Discussionmentioning
confidence: 99%